Effects of microwave heating on changes in chemical and thermal properties of vegetable oils - Tan, C. P.; Che Man, Y. B.; S., Jinap; Yusoff, M. S. A. (Wiley, 2001)
The effects of microwave heating on the cooling profiles of two vegetable oils (corn oil and soybean oil) were studied using differential scanning calorimetry (DSC) and compared to changes in chemical parameters. These oils were exposed for several periods of time to three controlled treatments: low-, medium-, and high-power settings, respectively. The DSC results were derived from the cooling curve of oils at a scanning rate of 5°C/min. The chemical analyses of the oils included peroxide value, anisidine value, free fatty acid content, iodine value, and C18∶2/C16∶0 peak area ratio. A statistical comparison was carried out between DSC and the chemical parameters. In general, correlations were good between these parameters. Likewise, the experimental data showed that, for a given microwave power setting, a good correlation existed between DSC curve parameters and heating periods. These results indicate that DSC can be used as an objective nonchemical, instrumental technique to monitor lipid oxidation in both traditionally heated and microwave-heated oils.